2017
DOI: 10.1128/jcm.02459-16
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Clinically Relevant Members of the Genus Exophiala by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry and Description of Two Novel Species, Exophiala campbellii and Exophiala lavatrina

Abstract: is a ubiquitous pleomorphic genus comprising at least 40 species, many of which have been associated with superficial, visceral, or systemic infections in humans, other mammals, or cold-blooded animals. In this study, we investigated the potential of matrix-assisted laser desorption-ionization time of flight mass spectrometry (MALDI-TOF MS) for the identification of species. A total of 89 isolates (including 50 human and 4 animal clinical isolates) stored in the National Collection of Pathogenic Fungi were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…In the past few decades, several case reports have been published on invasive fungal infections caused by melanized fungi . However, extensive multicentric studies containing a large number of clinical isolates identified by MALDI was only published by Singh et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, several case reports have been published on invasive fungal infections caused by melanized fungi . However, extensive multicentric studies containing a large number of clinical isolates identified by MALDI was only published by Singh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported an MALDI‐TOF MS‐based identification of bacteria, yeast, and hyaline fungi . However, only a few studies have reported a MALDI‐based identification of melanized fungi due to the lack of a standardized protein extraction protocol and a limited database availability . In addition, the present Bruker database contains very few entries of melanized fungi.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of previous reports have highlighted the importance of supplementing the commercial databases supplied with the various MALDI-TOF platforms with appropriate reference MALDI-TOF spectra in order to improve identification success (29)(30)(31)(32). Since none of the 10 known species included in the test panel employed here were represented in the latest Bruker MSP database, appropriate reference spectra were generated and added to the commercial database.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we recently demonstrated that MALDI-TOF MS could reliably discriminate between a wide variety of clinical and environmental Exophiala species (32). However, in all cases identification accuracy is limited by the availability of appropriate reference MALDI-TOF spectra in the commercial databases supplied with the various MALDI-TOF platforms (29)(30)(31)(32). Here we evaluated whether MALDI-TOF MS could be used to differentiate a variety of filamentous fungi implicated in black-grain eumycetoma and related subcutaneous clinical syndromes.…”
mentioning
confidence: 99%
“…The ITS sequences of representative Exophiala species and relatives were obtained from GenBank based on BLASTn searches and on the datasets of Yong et al (12) and Borman et al (13). The sequences were assembled and aligned using MUSCLE (14) as implemented in Sequencher version 5.4.6-Build 46289 (Gene Codes Corp., MI USA) and refined visually using SE-AL (15).…”
Section: Post-mortem Diagnosticsmentioning
confidence: 99%